2019
DOI: 10.3390/w11051003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flooding on Evaporation and the Groundwater Table for a Salt-Crusted Soil

Abstract: Soil salt crusts have been shown to have a strong influence on evaporation and water movement in soils, and this has attracted considerable attention. However, there is little information available on these processes during flooding. The objective of this study was to investigate the evaporation rate, variation in the groundwater table, and soil water content of salt-crusted soil flooded by five floodwater depths: 2 mm (Treatment A), 6 mm (Treatment B), 10 mm (Treatment C) 14 mm (Treatment D), and 18 mm (Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Salt precipitation by NaCl tends to lead to the creation of salt domes over the matrix surface, causing the disconnect between the matrix surface and the salt crust (Dai et al, 2016). In this study, the salt crust was elevated and formed a salt dome (Figures 4 and 6); this is also known as the blistering phenomenon (Licsandru et al, 2019), which has been a concern in recent years, and has been reported in sandy clay loam, silty soils, silt loam, sand, and glass beads (Dai et al, 2016;Li & Shi, 2019;Licsandru et al, 2019;Nachshon et al, 2018).…”
Section: Ss1 Ss2 Ss3 Ss4mentioning
confidence: 55%
See 3 more Smart Citations
“…Salt precipitation by NaCl tends to lead to the creation of salt domes over the matrix surface, causing the disconnect between the matrix surface and the salt crust (Dai et al, 2016). In this study, the salt crust was elevated and formed a salt dome (Figures 4 and 6); this is also known as the blistering phenomenon (Licsandru et al, 2019), which has been a concern in recent years, and has been reported in sandy clay loam, silty soils, silt loam, sand, and glass beads (Dai et al, 2016;Li & Shi, 2019;Licsandru et al, 2019;Nachshon et al, 2018).…”
Section: Ss1 Ss2 Ss3 Ss4mentioning
confidence: 55%
“…(2016) found that the salt crust in their experiments showed upward movement at a rate of 5 μm h −1 along the walls of the plastic tube. Li and Shi (2019) also reported that the salt crust was elevated, forming domes over the surface of silt loam soils. The formation of the air layer due to the elevated salt crust is assumed to prevent local water transport by capillary flow (Licsandru et al., 2019).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Salt crusts are a typical soil structure that forms as a consequence of soil enrichment and bonding due to salt accumulation [12]. Soil salt crusts are a type of soil surface crust that usually exhibits high concentrations of salt, and they are observed in arid lands with shallow groundwater tables [13][14][15].…”
Section: Introductionmentioning
confidence: 99%